2020
DOI: 10.7759/cureus.8283
|View full text |Cite
|
Sign up to set email alerts
|

Closed Incision Negative Pressure Therapy Achieves Better Outcome Than Standard Wound Care: Clinical Outcome and Cost-Effectiveness Analysis in Open Ventral Hernia Repair With Synthetic Mesh Positioning

Abstract: Background Surgical site infections (SSIs) and surgical site occurrences (SSOs) are frequent post-operative complications that are dependent on the presence of different risk factors. The use of closed incision negative pressure therapy (ciNPT) is considered a measure by the WHO guidelines for prevention of SSIs. The prevention of SSOs is an extremely important issue in the ventral hernia repair (VHR) surgical field. SSO onset not only affects the patient's quality of life, but can also cause the onset of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Eight papers were identified in this review that exclusively addressed prophylactic incisional (closed-wound) negative pressure wound therapy after ventral hernia repair. One had to be discarded because a full text was not found (27)(28)(29)(30)(31)(32)(33). All studies seem consistent in reporting lower rates of SSI and SSO when using pNPWT (Table 3).…”
Section: Prophylactic Negative Pressure Wound Therapy (Pnpwt)mentioning
confidence: 98%
“…Eight papers were identified in this review that exclusively addressed prophylactic incisional (closed-wound) negative pressure wound therapy after ventral hernia repair. One had to be discarded because a full text was not found (27)(28)(29)(30)(31)(32)(33). All studies seem consistent in reporting lower rates of SSI and SSO when using pNPWT (Table 3).…”
Section: Prophylactic Negative Pressure Wound Therapy (Pnpwt)mentioning
confidence: 98%
“…The administration of hemostatic agents in the surgical pocket improves postoperative healing reducing the hematoma formation rate. The use of closed incision negative pressure systems (ciNPTs) helps prevent SSIs and CIEDs removal [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Removal of an infected CIED can be performed either by percutaneous lead traction through the generator pocket or by a surgical approach [ 34 ]. The use of advanced medications, such as ciNPT and vacuum-assisted closure (VAC) therapy, can be considered to improve healing [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…11 The use of incisional negative pressure wound therapy (iNPWT) reduces the risk of SSI in multiple specialties, including colorectal surgery, vascular surgery, and plastic surgery. [12][13][14][15][16][17][18] A systematic review and meta-analysis of studies comparing iNPWT with the standard of care in the reduction of SSIs demonstrated a statistically significant reduction in SSI for all 7 subgroup analyses conducted. 19 In orthopaedic surgery, iNPWT reduces the risk of SSI in lower extremity fractures, primary and revision arthroplasty, hip and knee periprosthetic fractures, and hemiarthroplasty following femoral neck fractures.…”
Section: Introductionmentioning
confidence: 99%